(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2020)
Mangrove ecosystems can be affected by pollutants that humans generate when released into wastewater and that are downstream transported by rivers, among those, heavy metals have received the most attention because they have a high toxicity and are not biodegradable. Cadmium is a polluting heavy metal that may affect coastal marine ecosystems, that is considered one of the most harmful due to the high degree of toxicity, solubility and ability to concentrate and incorporate into the food web. Consequently, it is of high importance to determine the effect that Cd has on germination and growth in different species of mangrove trees as Rhizophora mangle, Hilairanthus germinans and Conocarpus erectus. A total of 1,176 hypocotyls and propagules were obtained, those were sterilized and submitted to realistic Cd concentrations of 0.25, 0.50, 1, 2, 4 and 8 ppm, using distilled water as a positive control. The growth stimuli of hypocotyl length did not present significant differences between the concentrations studied of Cd. The length of the radicle in higher concentrations of Cd presented null values in terms of growth. The germination percentage values in the different Cd concentrations in the studied species were significantly lower than the control. Finally, the FII showed that toxicity occurred in all concentrations of Cd and that it can be concluded that Cd is toxic to Rhizophora mangle, Hilairanthus germinans and Conocarpus erectus at levels permitted in the regulations. Therefore, it is recommended to reduce the maximum permissible limit of Cd toxicity in Ecuador.